О конверсии и флективном словообразовании - Англицкас, Вайдотас (Kalbotyra, 1987)
The study of English and Lithuanian non-affixal deverbal nouns shows that conversion in English and inflectional derivation in Lithuanian are two different ways of word-formation. The creation of a word through conversion involves the formation of a new word stem without using any formal means within the word, the inflection having the only function – that of distinguishing between different words and forms. In Lithuanian a new word may be coined through change of the paradigm, one and the same stem being used for the formation of categorically different words.